Methodology for the Use of our National Heritage in the Upbringing of Spiritual Moral Qualities of Primary School (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Multimedia is a necessary element of computers, a sound board that processes sound. To the sound board, a means of producing sound, acoustic systems or single listeners, as well as microphones that serve to enter audio data are connected. Other audio components such as a tape recorder, electric musical instruments can also be connected to the sound board.